2017
DOI: 10.1128/cmr.00033-16
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations, Treatment, and Diagnosis of Tropheryma whipplei Infections

Abstract: SUMMARY Whipple's disease is a rare infectious disease that can be fatal if left untreated. The disease is caused by infection with Tropheryma whipplei, a bacterium that may be more common than was initially assumed. Most patients present with nonspecific symptoms, and as routine cultivation of the bacterium is not feasible, it is difficult to diagnose this infection. On the other hand, due to the generic symptoms, infection with this bacterium is actually quite often in the differential diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
182
2
48

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(235 citation statements)
references
References 224 publications
3
182
2
48
Order By: Relevance
“…WD can mimic lymphoproliferative disorders, malabsorption syndromes or rheumatic diseases [1,2] . The clinical spectrum of WD includes four types of manifestations: the classic form with chronic diarrhoea, abdominal pain, weight loss and arthralgias; the localized type, including endocarditis, uveitis, lymphadenitis and neurological manifestations; acute self-limited infections, such as acute gastroenteritis or pneumonia; and finally, the asymptomatic healthy carriers [3] . The prevalence of mesenteric lymphadenopathy in Whipple's disease is reported to be 17% [2] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WD can mimic lymphoproliferative disorders, malabsorption syndromes or rheumatic diseases [1,2] . The clinical spectrum of WD includes four types of manifestations: the classic form with chronic diarrhoea, abdominal pain, weight loss and arthralgias; the localized type, including endocarditis, uveitis, lymphadenitis and neurological manifestations; acute self-limited infections, such as acute gastroenteritis or pneumonia; and finally, the asymptomatic healthy carriers [3] . The prevalence of mesenteric lymphadenopathy in Whipple's disease is reported to be 17% [2] .…”
Section: Discussionmentioning
confidence: 99%
“…The gold standard diagnostic test used to be PAS staining of duodenal biopsy specimens, but this has poor specificity and sensitivity [3] . PCR has led to an expansion in diagnostic capacity, especially in localized WD with lymphadenitis, as reported in this case [1] .…”
Section: Discussionmentioning
confidence: 99%
“…Biagi et al reports that there is no consensus about which one is the best therapy for WD, but standard therapy (ceftriaxone TMP-SMZ) for the first year(s) and then lifelong doxycycline seems to be a reasonable option [5, 15]. Dolmans et al [16] reviewing the recent literature reported an alternative approach involving “doxycycline (200 mg/day) and hydroxychloroquine (600 mg/day) for 12 months and for localized T. whipplei infection, treatment with doxycycline (200 mg/day) and hydroxychloroquine (600 mg/day) for 12 to 18 months.” In our case, both the specialists consulted and agreed for the first mentioned therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Referring to immunosuppressive therapies that can alter or induce a false diagnosis of WD [11, 16], our patient has never had those kind of treatments for her breast carcinoma nor for the more recent knee pain she suffered before WD diagnosis was made. As reported by T. Marth, immunosuppressive drugs especially tumour necrosis factor inhibitor (TNFI) may influence the clinical course of T. whipplei infection [9, 11] leading to WD.…”
Section: Discussionmentioning
confidence: 99%
“…7d) and PAS-D [79]. The differential diagnosis includes Tropheryma whipplei, the causative agent of Whipple disease [80]. These bacilli are PAS-D positive, but acid fast-negative.…”
Section: Mycobacteriamentioning
confidence: 99%